Correction: Lee et al. Demyristoylation of the Cytoplasmic Redox Protein Trx-h2 Is Critical for Inducing a Rapid Cold Stress Response in Plants. Antioxidants 2021, 10, 1287 - Eun Seon Lee; Joung Hun Park; Seong Dong Wi; Ho Byoung Chae; Seol Ki Paeng; Su Bin Bae; Kieu Anh Thi Phan; Min Gab Kim; Sang-Soo Kwak; Woe-Yeon Kim; Dae-Jin Yun; Sang Yeol Lee (MDPI AG, 2022)
In the original publication [...]